Metode dan Teknik Supervisi Pendidikan di Mal UINSU - Fadhil Ahmad Zaky; Farhana Farhana; Hafiz Yusuf Nasution; Khoirunnisa Fadila Rambe; Nurul Sufni; Inom Nasution (Prodi Perpustakaan dan Sains Informasi, 2023)
This journal reviews the Methods and Techniques of Educational Supervision at the UINSU MAL. This study aims to determine the methods and techniques carried out by the Principal as a supervisor which are implemented in educational supervision at MAL UINSU Medan. Methods and techniques of educational supervision are the methods and tools used by supervisors to achieve the goals of the supervision itself which in the end can make teaching improvements according to the situation and conditions. The research instruments are observation, interviews and documentation studies. The source of the data from the results of this study was the results of interviews with the Principal of the MAL UINSU School, namely Dr. Zunaidar Sinaga M.Pd. the results of the research conducted show that the method or approach used by the principal as an educational supervisor is adjusted based on the performance characteristics of each teacher in order to achieve the planned educational goals. The method used is direct action, a way of approaching problems that are direct.